Development of a Monte Carlo multiple source model for inclusion in a dose calculation auditing tool. Issue 9 (1st August 2017) - Faught, Austin M.; Davidson, Scott. E.; Fontenot, Jonas; Kry, Stephen F.; Etzel, Carol; Ibbott, Geoffrey S.; Followill, David S.
Abstract : Purpose: The Imaging and Radiation Oncology Core Houston (IROC‐H) (formerly the Radiological Physics Center) has reported varying levels of agreement in their anthropomorphic phantom audits. There is reason to believe one source of error in this observed disagreement is the accuracy of the dose calculation algorithms and heterogeneity corrections used. To audit this component of the radiotherapy treatment process, an independent dose calculation tool is needed. Methods: Monte Carlo multiple source models for Elekta 6 MV and 10 MV therapeutic x‐ray beams were commissioned based on measurement of central axis depth dose data for a 10 × 10 cm 2 field size and dose profiles for a 40 × 40 cm 2 field size. The models were validated against open field measurements consisting of depth dose data and dose profiles for field sizes ranging from 3 × 3 cm 2 to 30 × 30 cm 2 . The models were then benchmarked against measurements in IROC‐H's anthropomorphic head and neck and lung phantoms. Results: Validation results showed 97.9% and 96.8% of depth dose data passed a ±2% Van Dyk criterion for 6 MV and 10 MV models respectively. Dose profile comparisons showed an average agreement using a ±2%/2 mm criterion of 98.0% and 99.0% for 6 MV and 10 MV models respectively. Phantom plan comparisons were evaluated using ±3%/2 mm gamma criterion, and averaged passing rates between Monte Carlo and measurements were 87.4% and 89.9% for 6 MV and 10 MV models respectively. Conclusions: Accurate multiple source models for Elekta 6 MV and 10 MV x‐ray beams have been developed for inclusion in an independent dose calculation tool for use in clinical trial audits.